Bone density in ankylosing spondylitis assessed by dual energy X-ray absorptiometry and quantitative ultrasound: The relationship of bone mineral density with functional and disability status - Ozgocmen, S; Kaya, A; Kamanli, A; Ardicoglu, O (Springer London Ltd, 2004)
[Abstract Not Available]
IOF World Congress on Osteoporosis -- MAY 14-18, 2004 -- Rio de Janeiro, BRAZIL